Antiproliferative effect of gynura procumbens (lour.) Merr. Leaves etanolic extract on 7,12-dimethylbenz(a)antracene induced male rat liver - Edy Meiyanto; Retno Murwanti; Adam Hermawan; Fithriyatun Nisa (Tabriz University of Medical Sciences, 2012)
Purpose: The leaves of Gynura procumbens (Lour.) Merr. has been traditionally used as anticancer. Ethanolic extract of G. procumbens leaves (EGP) showed cytotoxic activity and anticancer activity in animal cancer model. This study was conducted to observe antiproliferative effect using male rat's liver cells induced by 7,12-dimethylbenz(a)antracene (DMBA). Methods: Forty days old Sprague Dawley male rats were divided into 4 groups, (1) 0.5 % CMC Na, (2) 20 mg/kg BW DMBA p.o ten times in three weeks, (3) DMBA+300 mg/kg BW of EGP, and (4) DMBA+750 mg/kg BW of EGP. The extract was dissolved into 0.5 % CMC-and administered daily per oral one week before, during and terminated 1 week after the DMBA induction. After sixthteen week experiment, rat livers were sectioned and stained with Haematoxyllene and Eosin (H&E) and AgNOR. Results: Histopatology profile showed no primary liver tumor on DMBA group. mAgNOR value of DMBA+300 mg/kg BW EGP showed significant antiproliferative effect compared to DMBA group. Conclusion: Ethanolic extract of G. procumbens leaves showed antiproliferative activity on male rats liver induced by DMBA.